2018
DOI: 10.1002/cam4.1662
|View full text |Cite
|
Sign up to set email alerts
|

Circumferential resection margin as a prognostic factor after rectal cancer surgery: A large population‐based retrospective study

Abstract: AimThis study aimed to investigate circumferential resection margin (CRM) as a prognostic factor for long‐term oncologic survival after rectal cancer surgery.MethodsPatients diagnosed with malignant rectal cancer between 1 January 2010 and 31 December 2014, from the Surveillance, Epidemiology, and End Results (SEER) program were identified for this study. The patients were divided into five CRM groups to compare the baseline characteristics and assess cancer‐specific survival (CSS): 0‐1 mm, 1.1‐2.0 mm, 2.1‐5.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 38 publications
2
30
1
Order By: Relevance
“…The study showed that a tumor circumferential resection margin of less than 2 mm were associated with signi cantly poorer patient survival. This nding was consistent with a great deal of other literature (6,8) and what is accepted in our current clinical practice. The distal resection margin was, not shown to be an independent predictor of survival.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The study showed that a tumor circumferential resection margin of less than 2 mm were associated with signi cantly poorer patient survival. This nding was consistent with a great deal of other literature (6,8) and what is accepted in our current clinical practice. The distal resection margin was, not shown to be an independent predictor of survival.…”
Section: Discussionsupporting
confidence: 92%
“…The rst is more invasive, while the other is potentially sphincter sparing (SSR). The main aims of modern CRC surgery is to establish a su cient distal and circumferential resection margin (DRM and CRM), as an incomplete resection (any positive resection margin) is the main risk factor for a lethal local reccurance (5)(6)(7). The current gold standard is the principle of total mesorectal excision (TME), which aims to reduce lymphatic spread (introduced by Heald and originated from the observations of Moynihan) (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…In later studies, CRM involvement was found to increase the risk of local recurrence and distant metastases and to adversely affect survival rates [ 36 , 37 ]. The distance of CRM has a correlation with survival and local recurrence [ 38 ] and recommendation is 2 mm [ 39 ]. This study showed result in the same correlation but limitation did not record the location of tumor for correlation with CRM.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al demonstrated CRM ≤1 mm was independently associated with 99% increased risk of cancer-specific mortality in rectal cancer and CRM (5.1-10.0 mm) was independently associated with 29.2% decreased risk of cancer-specific mortality. 28 Kelly et al 29 showed CRM clearance of 5 mm or less had a worse outcome, and therefore, CRM clearance of more than 5 mm should be achieved in order to optimize curative treatment where overall 5-year survival rates for ≤1 mm, 1 to 5 mm, 5 to 10 mm, ≤10 mm were 43.2%, 51.7%, 66.6%, and 66.0%, respectively. Lucovnik and Omejc 30 showed 5-year survival was adversely affected by CRM of <2 mm compared with >2 mm.…”
Section: Discussionmentioning
confidence: 99%